CRITICAL REVIEW OF ALBERT BANDURA'S SOCIAL COGNITIVE THEORY IN THE SUSTAINABILITY OF THE MUHAMMADIYAH STUDENT ASSOCIATION CADRE - Saputra, Ezat Indra; Fajri, Lalu Muhammad (Prosiding University Research Colloquium, 2024)
"This research aims to review the sustainability of the IMM cadre and see to what extent Albert Bandura's Social Cognitive theory can be used as an alternative cadre model at IMM Surakarta. This research is classified as descriptive qualitative research. The data in this research is in the form of cadre documents and interview results. Data was collected using literature study and interview techniques. The data that has been collected is analyzed using content analysis techniques. The results of this research are that the Application of Social Learning in the Learning Process in Albert Bandura's cadre works provides space for a continuous learning process. Continuous movements encourage the emergence of problems and encourage intellectuals to formulate new proposals for action. Prioritizing environmental influences, prioritizing parts, prioritizing the role of response, prioritizing mechanisms for forming learning outcomes through stimulus-response procedures. Albert Bandura's learning process emphasizes the role of previously formed skills and the formation of habits through practice and repetition. The learning outcome achieved is the emergence of the desired behavior. Thus, Albert Bandura's Social Cognitive Theory can be used as a cadre model at IMM. Keywords: Cadre 1; Social Cognitive 2; Muhammadiyah Student Association 3 "